2017
DOI: 10.1038/nrm.2016.143
|View full text |Cite
|
Sign up to set email alerts
|

Functions of bromodomain-containing proteins and their roles in homeostasis and cancer

Abstract: Bromodomains (BRDs) are evolutionarily conserved protein-protein interaction modules that are found in a wide range of proteins with diverse catalytic and scaffolding functions and are present in most tissues. BRDs selectively recognize and bind to acetylated Lys residues - particularly in histones - and thereby have important roles in the regulation of gene expression. BRD-containing proteins are frequently dysregulated in cancer, they participate in gene fusions that generate diverse, frequently oncogenic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
473
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(506 citation statements)
references
References 191 publications
9
473
0
3
Order By: Relevance
“…JQ1 and other inhibitors of epigenetic (BET- (72,73). BETcontaining proteins recognize specific acK residues on histones and transcription factors such as NF-κB (32)(33)(34)(35)72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JQ1 and other inhibitors of epigenetic (BET- (72,73). BETcontaining proteins recognize specific acK residues on histones and transcription factors such as NF-κB (32)(33)(34)(35)72).…”
Section: Discussionmentioning
confidence: 99%
“…BETcontaining proteins recognize specific acK residues on histones and transcription factors such as NF-κB (32)(33)(34)(35)72). Recent seminal studies by Chen et al (30,31), using A549 lung cancer cells, revealed that Brd4 binding to acK310 on the p65 subunit of NF-κB maintains the latter in an active form.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to BPTF, there are more than 40 diverse proteins containing BRDs; 57 65 Notably, based on promising results in murine models, BRD proteins have become targets for drug development and translation. 66,67 In aggregate, we propose that haploinsufficiency of BPTF results in an augmented neuronal death, which likely occurs mainly during the postnatal period and manifests with acquired microcephaly and neurodevelopmental abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…This results in a relative opening of chromatin, and histone acetylation is broadly associated with activate transcription. Acetylated lysine residues are “read” or recognized by bromodomain-containing proteins, which in addition to a bromodomain, often contain a variety of other functional domains that allow for HAT activity, DNA binding, histone methyltransferase activity, helicase activity, ATPase activity and more (reviewed in (81)).…”
Section: Regulation Of Chromatin Modification By Endogenous Metabolitmentioning
confidence: 99%